Expanding learning spaces and processes in agroindustry through system dynamics - Angarita-Zapata, Juan Sebastian; Vásquez Cardozo, Carlos A.; Andrade-Sosa, Hugo H. (Universidad Pedagógica y Tecnológica de Colombia, 2019)
An integration strategy is proposed for modeling and simulation of System Dynamics in the Agroindustry program provided by the Institute of Distance Education and Regional Projection of the Universidad Industrial de Santander. The design and implementation of the strategy was carried out through an experiences-based experiment involving teachers and students enrolled in the Animal Nutrition Management course of the agroindustrial program. Such experiences were focused on the use of learning environments in class to complement theoretical knowledge by implementing simulated experiments enabling this knowledge to get closer to real experiences on-site. From this experiences-based experiment and the proposed strategy, it is possible to conclude that learning environments allow decision-making capacities to be developed with the support of simulation scenarios that are very close to the reality on the field.